On a new species of freshwater crab from southern China (Crustacea, Brachyura, Potamidae) - Shi, Boyang; Pan, Da; Sun, Hongying (Zootaxa, 2023)
A new species of potamid freshwater crab of the genus Indochinamon Yeo & Ng, 2007, is described from a recent collection in Yunnan Province, China. Indochinamon frontatum sp. nov. is distinguished from congeners by the form of the carapace, notably in the features of the convex frontal region, and distinctively structured male first gonopod. Molecular data derived from the mitochondrial 16S rDNA supports the recognition of the taxon.